Development of an Adaptive Routing Mechanism in Software-Deﬁned Networks - A. N. Noskov; I. A. Manov (Моделирование и анализ информационных систем, 2015)
The purpose of this work is to develop a unitary mechanism of adaptive routing of diﬀerent kinds, basing on the current requirements on the quality of service. The software conﬁguration of a network is the technology of the future. The trend in communication systems constantly conﬁrms this fact. However, the application of this technology in its current form is justiﬁed only in large networks of technology giants and telecom operators. Today we have a large number of dynamic routing protocols to route big volume traﬃc in communication networks. Our task is to create the solution that can use the opportunities of each node to make a decision on the transmission of information by all possible means for each type of traﬃc. Achieving this goal is possible by solving the problem of the development of generalized metrics, which details the links between devices in the network, and the problem of establishing a framework of adaptive logical network topology (route management) to ensure the quality of the whole network in order to meet the current requirements on the quality of a particular type service.